Metabolomic and Transcriptomic Analysis of the Mechanism of the Apple Coloration Change After Uncovering Fruit Bag - Pengwei Duan; Xiaojian Ma; Haiqiang Shi; Lizhe Qin; Jizhuang Du; Sumiao Yang; Jianjun Zhang (International Journal of Fruit Science)
Coloring is an important external quality of apples. Commercial apple varieties are bagged before the fruits ripen to ensure they grow in a pesticide-free environment, including preventing mechanical damage, reducing sunburn, etc. When the apple reaches the green fruit stage, the bag can be uncovered until it ripens and the peel is colored. There are two color patterns of “Fuji” apple peels (stripe and blush). In this study, the pattern of metabolite accumulation and gene expression was profiled in the striped and blushed apple peels at three ripening periods to elucidate the color formation mechanism within two weeks after removing the bag. The phenotypes presented in the peel coloring process are different between SF (stripe red) and HM (blush red), which have different accumulated levels of metabolites and gene expression during the coloring process. At the green fruit stage, a total of 83 differentially accumulated metabolites and 674 differentially expressed genes were identified between SF and HM. At the color turning stage, 48 DAMs and 880 DEGs were identified, including 20 flavonoids and 17 related genes. At the complete coloring stage, 95 DAMs and 2258 DEGs were identified, including 34 flavonoids and 23 related genes. In this study, a total of 10 kinds of key anthocyanins were found in the apple peel color-turning process. Keracyanin and cyanin were accumulated significantly at the apple color-turning period, while cyanidin-3-O-(6’’-O-malonyl) glucoside was accumulated at the complete coloring period. These key metabolites and related regulatory genes are responsible for the stripe and blush color formation in apple peel after uncovering the fruit bag.